Strategic learning: a task for the mediator teacher - De La Cruz Apari, Julissa (2017)
Strategic learning is the search for meaningful learning of content, skills and abilities development with the principle of the students as self-regulating entities of their own learning process. The teacher as one of the participants of the educational process must be trained and prepared to offer different strategies to the student according to his/her style, learning pace or educational need. Nowadays, the main concern for educational institutions is to have teachers capable of organizing strategic learning sessions, as they facilitate the process and encourage the student to be the owner and builder of his/her own knowledge. It is vitally important to take into account that this type of learning will not produce any kind of change if the teacher who imparts it is just a simple information transmitter. It is the responsibility of the mediator teacher to develop in the students the ability to use appropriate strategies according to each educational requirement.